Productivity Analysis Towards Lean Manufacturing at a Textile Manufacturing Company - Abdullah, Rohana; Mohamad, Effendi; Mohamad, Nor Akramin; Saptari, Adi (2009)
Changes continually occuring in the industry and business environment must be considered both economically and practically.Manufacturing is inherently a complex task and stems from various aspects to create productive manufacturing environment.This research is an attempt to analyze the productivity of a packing production line. The approach taken was first to focus on performing work study on the main processes activity and classifying them into value added and non value added activities. The information gathered was then used to evaluate opportunities for improvement to be suggested to the management.Among the improvement identified were the shaking machine efficiency, method to weigh the pins and material preparation operator. Study was also done to evaluate opportunity to send material for packing to the external vendor which can result in tremendous savings for the company. The findings from this study were shared with the company’s management to assist their effort in improving the productivity to remain competitive and achieving lean manufacturing in the currently challenging global market.